Egg-sploring the unusual: ICSI in Klippel-Trenaunay-Weber syndrome - Sathyamurthy, Kaavya; M., Kundavi K.; V., Geetha; Rashmi; R., Geovin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Klippel-Trenaunay-Weber syndrome (KTWS) is a rare congenital vascular disorder characterized by capillary malformations, venous and lymphatic anomalies, and soft tissue or bone overgrowth. Patients with KTWS face unique challenges in assisted reproductive technology (ART) due to their hypercoagulable state and the presence of extensive vascular malformations. Pregnancy can exacerbate these vascular complications, increasing maternal morbidity and mortality. In vitro fertilization (IVF) with gestational surrogacy offers a safer reproductive option. A 34-year-old woman with KTWS, a history of intermittent rectal bleeding, and extensive vascular malformations presented with primary infertility. Clinical and diagnostic evaluation revealed a reasonable ovarian reserve (AMH: 1.08 ng/ml) but significant vascular abnormalities in the mesenteric, splenic, hepatic, and colonic vasculature. A multidisciplinary approach was undertaken to minimize the risks associated with ovarian stimulation and oocyte retrieval. A GnRH antagonist protocol was chosen, with a dual trigger (Decapeptyl 200 mcg and hCG 10,000 IU) and careful anticoagulation management using low molecular weight heparin (LMWH). Nine mature oocytes were retrieved and cryopreserved without complications, and the patient was advised to proceed with gestational surrogacy. This case highlights the complexities of fertility management in patients with KTWS. The successful oocyte retrieval in a high-risk vascular patient demonstrates that, with meticulous planning and individualized care, ART can be safely performed. A multidisciplinary strategy, including anticoagulation adjustments and perioperative monitoring, is crucial in achieving favourable reproductive outcomes while minimizing risks. This case adds to the limited literature on ART in KTWS, reinforcing the feasibility of fertility preservation through a well-planned, multidisciplinary approach.